The geomagnetic measurements at the Hurbanovo Geomagnetic Observatory in year 2006 - VÁCZYOVÁ, Magdaléna (Contributions to Geophysics and Geodesy, 2008)
In this paper we present the results of geomagnetic observations performed at the Geomagnetic Observatory GPI SAS at Hurbanovo in 2006. In 1998 the observatory obtained the status of the INTERMAGNET Magnetic Observatory (IMO). From this time we send the minute mean values of the geomagnetic components X, Y and Z to the Edinburgh and Paris GINs every day. Our final data have been included in the yearly INTERMAGNET CD-ROM